Human Capital-Economic Growth Nexus in Africa: Heteregeneous Panel Causality Approach - Emmanuel Anoruo; Uchenna Elike (International Journal of Economics and Financial Issues, 2015)
This paper examines the causal relationship between human capital (HC) and economic growth (EG) for a panel 29 African countries. In particular, the study applied theoretically consistent panel unit root procedures and panel co-integration tests that account for the presence of cross-sectional dependency among the members of a panel. To ascertain the direction of causality between HC and EG, the study applies the heterogeneous panel causality test proposed by Dumitrescu and Hurlin. This test has the ability to control for the presence of both heterogeneity and cross-sectional dependence that might be present in the panel. To determine the signs of the relationship between the two variables, the study applied the dynamic ordinary least square (OLS). The results from the heterogeneous panel causality test provide evidence in support of bidirectional causality between HC and EG for the sample countries. The results from the dynamic OLS indicate that HC and EG have significantly positive effect on each other. This finding reinforces the need for the sample countries to work in tandem in promoting education as an engine of EG.